Investigação dos processos fonte-sumidouro do ozônio troposférico na RMRJ: abordagem teórica e computacional - Silva, Mauricio Soares da (2019)
The high ozone concentrations in the low troposphere are one of the biggest problems related to air quality in the world. In the Metropolitan Region of Rio de Janeiro (MRRJ), it is revealed that in approximately 1/3 days of the year, the national standard of air quality for ozone is exceeded. Motivated by this degrading condition, was investigated the mechanisms of production and consumption of tropospheric ozone in the different subregions of the MRRJ. To this end, was adopted statistical, theoretical and computational approaches that, in an integrated manner, enabled answering questions related to ozone. From the proposition of six homogeneous regions in terms of ozone concentrations in MRRJ, was demonstrated that some of these are characterized essentially by the production, while others by the consumption of ozone. It was also observed that, even if they are not producers, some regions are degraded by transporting the pollutant from the producing regions. In general, the approaches showed that the influence of nitrogen oxides overlaps the volatile organic compounds in the chemical kinetics of ozone present in MRRJ.